Financial globalization: some conceptual problems - Philip Arestis; Santonu Basu (Levy Economics Institute of Bard College, 2002)
In recent years free movement of financial capital following financial liberalization has given the impression that financial markets are truly globalized. In this paper we argue that free movement of financial capital alone does not constitute financial globalization. To achieve true financial globalization, an important requirement is the creation of a worldwide single currency, managed by a single international monetary authority. This condition, however, is not met under current institutional arrangements.
Keywords: 330